Critical exposure of successes of neoliberal reforms: the ‘renown’ case of Chile - Daemane, Moses, M. M.; Daemane, M.S.R.; Nyawo-Shava, Vongai Z. (Annals of Humanities and Development Studies, 2016)
This paper critically examines the ‘success’ of neoliberal reforms in one developing country under the true light of succumbing, disempowered and disenfranchised labour sector and the needy, contradictions of such ‘success’ where the ‘state’ actually expropriated the society of fundamental self-determinism within the economy and authoritatively entrenched liberalization repressing society’s vigor, needs and interests. The state cannot serve the society’s needs by social possession demolition. The paper is written within clear global context whereby no developed country practices neoliberalism without overwhelming social entitlements from the state. Such states are called ‘successful/prosperous/developed’ liberal states, which, in practice, are ‘welfare states’. The true global-trade context is such that ‘Structural Adjustment- Lending-Programmes’- a lending conditionality by Wood’s Institutions are for the poor countries to trade with heavily subsidizing countries to deny the former ‘fair’ competition and equitable business shares and opportunities to alleviate their poverty. Hence, the paper answers why neoliberal reforms are unduly said to have produced a sustainable market economy in Chile but not in other countries. This is accomplished through the analytic questioning of the nature of the prevailing regime, relations among the different groups in society and state and society. If the Chilean state was correcting any wrong, then social possession is demolished.